Low Evolutionary Selection Pressure in Senescence Does Not Explain the Persistence of Aβ in the Vertebrate Genome - Moir, Robert D.; Tanzi, Rudolph E. (Frontiers in Aging Neuroscience, 2019)
The argument is frequently made that the amyloid-β protein (Aβ) persists in the human genome because Alzheimer's disease (AD) primarily afflicts individuals over reproductive age and, therefore, there is low selective pressure for the peptide’s elimination or modification. This argument is an important premise for AD amyloidosis models and therapeutic strategies that characterize Aβ as a functionless and intrinsically pathological protein. Here, we review if evolutionary theory and data on the genetics and biology of Aβ are consistent with low selective pressure for the peptide’s expression in senescence. Aβ is an ancient neuropeptide expressed by nearly all vertebrates. Consistent with unusually high evolutionary selection constraint, the human Aβ sequence is shared by 60 percent of vertebrate species and has been conserved across at least 400 million years. Unlike humans, the overwhelming majority of vertebrate species do not cease reproduction in senescence and selection pressure is maintained into old age. Hence, low selective pressure in senescence does not explain the persistence of Aβ across the vertebrate genome. The “Grandmother hypothesis” (GMH) is the prevailing model explaining the unusual extended postfertile period of humans. In the GMH, high risk associated with birthing in old age has lead to early cessation of reproduction and a shift to intergenerational care of descendants. The rechanneling of resources to grandchildren by postreproductive individuals increases reproductive success of decedents. In the GMH model, selection pressure does not end following menopause. Thus, evolutionary models and phylogenetic data are not consistent with the absence of reproductive selection pressure for Aβ among aged vertebrates, including humans. Our analysis suggests an alternative evolutionary model for the persistence of Aβ in the vertebrate genome. Aβ has recently been identified as an antimicrobial effector molecule of innate immunity. High conservation across the Chordata phylum is consistent with strong positive selection pressure driving human Aβ’s remarkable evolutionary longevity. Ancient origins and widespread conservation suggest the human Aβ sequence is highly optimized for its immune role. We detail our analysis and discuss how the emerging “Antimicrobial Protection Hypothesis” of AD may provide insights into possible evolutionary roles for Aβ in infection, aging, and disease etiology.